A Dozen Ways Of Love - Dougall, L. (Lily), 1858-1923 (Salt Lake City, UT : Project Gutenberg, 2006)
"A Dozen Ways Of Love" by L. Dougall is a collection of short stories written in the late 19th century. The book explores varying themes of love, including young love, marital connections, and societal relationships, likely reflecting the complex emotions intertwined with these experiences. Each chapter appears to delve into different aspects of love, with characters experiencing both joy and sorrow in their journeys. The opening of the first story, "Young Love," introduces a maid-servant approaching the residence of Mistress Macdonald on a dark November evening. Through her interactions with a local shopkeeper, we learn about Mistress Macdonald's deteriorating health and her family's struggles to cope with her decline. The narrative shifts between the maid's cheerful demeanor and the somber atmosphere surrounding the ailing matriarch, highlighting a contrast between youthful hope and lingering despair. As the characters grapple with memory, love, and loss, this opening sets the stage for reflections on the significance and complexities of love in different life stages. (This is an automatically generated summary.)
Young love -- A marriage made in heaven -- Thrift -- A taint in the blood -- 'Hath not a Jew eyes?' -- A commercial traveller -- The syndicate baby -- Witchcraft -- The girl who believed in the saints -- The pauper's golden day -- The soul of a man -- A freak of Cupid.
Release date is 2006-03-30
E-text prepared by Robert Cicconetti, Martin Pettit, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Fiction; Short stories